Care practices of older people with dementia in the surgical ward: A questionnaire survey. (11th November 2016) - Hynninen, Nina; Saarnio, Reetta; Elo, Satu
Objectives: The objective of this study was to describe the care practices of nursing staff caring older people with dementia in a surgical ward. Methods: The data were collected from nursing staff (n = 191) working in surgical wards in one district area in Finland during October to November 2015. Data were collected using a structured questionnaire and analyzed statistically. The instrument consists of a total number of 141 items and four dimensions. The dimensions were as follows: background information (12 of items), specific characteristics of older people with dementia in a surgical ward (24 of items), specific characteristics of their care in a surgical ward (66 of items) and use of physical restraints and alternative models for use of restraints for people with dementia (39 of items). Results: The questions which measure the nursing staff's own assessment of care practices when caring for people with dementia in surgical wards were selected: counseling people with dementia, reaction when a surgical patient with dementia displays challenging behavior and use of alternative approach instead of physical restraints. Most commonly the nursing staff pay attention to patient's state of alertness before counseling older people with dementia. Instead of using restraints, nursing staff gave painkillers for the patient and tried to draw patients' attention elsewhere. The nursing staff with longer work experience estimate that they can handle the patients' challenging behavior. They react by doing nothing more often than others. They pretend not to hear, see or notice anything. Conclusion: The findings of this study can be applied in nursing practice and in future studies focusing on the care practices among older people with dementia in acute care environment. The results can be used while developing patient treatments process in surgical ward to meet future needs.